2020
DOI: 10.1186/s12890-020-01356-8
|View full text |Cite
|
Sign up to set email alerts
|

Occult foreign body aspirations in pediatric patients: 20-years of experience

Abstract: Background The purpose of our study was to assess the frequency of occult foreign body aspiration (FBA) and to evaluate the diagnostic difficulties and therapeutic methods for these patients. Methods Between May 2000 and May 2020, 3557 patients with the diagnosis of FBA were treated in our department. Thirty-five patients with occult FBA were included in this study. A retrospective analysis of medical records was performed. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
0
8
1
2
Order By: Relevance
“…The present study also identified high risk demographic and clinical factors associated with dangerous EFB ingestion and complications. Contrary to previous studies identifying younger children as being at higher risk for foreign body ingestion, 2,37,38 we found that older children were at a higher risk of ingesting dangerous FBs. This may be due to increased manual dexterity as children develop and better mobility that permits them access to battery compartments of toys or previously inaccessible storage spaces in the home.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study also identified high risk demographic and clinical factors associated with dangerous EFB ingestion and complications. Contrary to previous studies identifying younger children as being at higher risk for foreign body ingestion, 2,37,38 we found that older children were at a higher risk of ingesting dangerous FBs. This may be due to increased manual dexterity as children develop and better mobility that permits them access to battery compartments of toys or previously inaccessible storage spaces in the home.…”
Section: Discussioncontrasting
confidence: 99%
“…Se excluyeron aquellos pacientes con una localización del cuerpo extraño distinta a la laringe, tráquea o árbol bronquial derecho o izquierdo y/o aquellos en los que el tiempo de enfermedad fue mayor de 18 días, considerando que tiempos mayores no serían emergencias pediátricas (13) . Los pacientes con ausencia de cuerpo extraño y las historias clínicas que no cumplieron con un llenado adecuado también fueron excluidas.…”
Section: Criterios De Exclusiónunclassified
“…A foreign body aspiration is a common event among paediatric patients. Children under 3 years of age are at the most risk due to their narrow airways and immature protective neuromuscular mechanisms [1]. Usually, the event is discovered by caregivers immediately due to a sudden attack of coughing, dyspnoea and wheezing in the child.…”
Section: Airway Obstructionmentioning
confidence: 99%